Diameter class distribution, growth and volume of Dryobalanops aromatica C.F. Gaertn. planted in Kenaboi Forest Reserve, Jelebu, Negeri Sembilan - Majuri, Setia (2016)
Dryobalanops aromatica C.F.Gaertn. was identified as a quality timber in Peninsular Malaysia and had an economic value. Dryobalanops aromatica were found productive for plantation programs where the programs is an alternative for a long-term timber production strategy in Peninsular Malaysia. A study was conducted in 1-ha area at Compartment 106, Kenaboi Forest Reserve, Jelebu, Negeri Sembilan to investigate the distribution of diameter class for Dryobalanops aromatica that are planted 45 years ago. A total ten plots, measuring in 50 m in length and 20 m in width were made in belt-transect method. The trees were categorized into diameter class and the number of the trees were recorded. Result shows that 116 trees was recorded and can be classified into four dbh classes which are dbh classes of 15 - 29.99 cm, 30 -44.99 cm, 45 - 59.99 cm and ≥ 60 cm. The number of individuals for dbh classes of 15 - 29.99 cm, 30 - 44.99 cm and 45 - 59.99 cm shows 12 individual (10.3%), 59 individual (50.9%) and 40 individual (34.5%) respectively. The dbh classes of ≥ 60 cm is the lowest with five individuals that only occupy only 4.3% of the area. Plot 2 shows the highest density of individuals with total 18 individual which consists all of dbh classes while Plot 6 shows the lowest number of individual with represent only eight individual. Mean dbh for the D. aromatica planted in Kenaboi FR is 41.73 cm. The MAI for the stands is ranging from 0.36 to 1.6 cm/yr. Total basal area for 1-ha area is 16.89 m2 with total volume is 221.77 m3 ha-1. The stands in the area shows the positively interaction between basal area (m2) and volume (m3) with y = 0.0623x + 0.071. The present study considered that the distribution of dbh classes in this area is poor because the number of survive trees is low compared to the number of planted trees in 1971.